31. HEALTH-RELATED QUALITY OF LIFE IN CHILDREN WITH CHRONIC DISEASES (Vietnam Journal of Community Medicine, 2025)
Objective: To assess the health-related quality of life in children with chronic diseases.Subjects and methods: A cross-sectional study was conducted on 132 children aged 2-16 years diagnosed with epilepsy or thalassemia at Saint Paul General Hospital. The Vietnamese version of the PedsQL™ 4.0 was used for assessment.Results: Children with thalassemia had significantly lower physical functioning scores than those with epilepsy (p < 0.001), while children with epilepsy had lower emotional functioning scores than those with thalassemia (p < 0.05). No significant differences were found between the two groups in overall health-related quality of life, social, or school functioning. Overall health-related quality of life was influenced by age, academic performance, disease duration, and treatment duration (p < 0.05), but not by sex or residential area (p > 0.05).Conclusion: Children with chronic diseases need targeted support to improve health-related quality of life, especially in physical aspects for those with thalassemia and emotional aspects for those with epilepsy. Further research is needed to better understand and enhance health-related quality of life in this population.
Keywords: Health-related quality of life, quality of life, children, epilepsy, thalassemia, PedsQLTM 4.0.